2015
DOI: 10.1192/pb.bp.113.043257
|View full text |Cite
|
Sign up to set email alerts
|

Specialist adult ADHD clinics in East Anglia: service evaluation and audit of NICE guideline compliance

Abstract: Aims and method To measure compliance with National Institute for Health and Care Excellence (NICE) recommendations in two adult attention-deficit hyperactivity disorder (ADHD) clinics and to guide further service development. We audited the case notes of 150 patients referred to adult ADHD clinics in East Anglia in 2010-2011 against NICE standards using an adapted version of the ADHD audit support tool.Results We found good compliance with NICE standards for diagnosis, assessment and pharmacological treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This is the first audit of a community CAMHS ADHD diagnostic pathway in SLaM, to our knowledge. Several audits have been published elsewhere in the UK, which have reported adherence to NICE guidelines for diagnosing ADHD in adults (Magon et al , 2015) and children (Bellenis et al , 2007; Coghill and Seth, 2015) referred to clinical services. The present study found that NICE (2008) recommendations for diagnosing ADHD in young people were generally consistent with existing clinical practice in most areas, with the audit identifying evidence that the four recommended guidance points were used least 90 per cent of cases eventually diagnosed with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first audit of a community CAMHS ADHD diagnostic pathway in SLaM, to our knowledge. Several audits have been published elsewhere in the UK, which have reported adherence to NICE guidelines for diagnosing ADHD in adults (Magon et al , 2015) and children (Bellenis et al , 2007; Coghill and Seth, 2015) referred to clinical services. The present study found that NICE (2008) recommendations for diagnosing ADHD in young people were generally consistent with existing clinical practice in most areas, with the audit identifying evidence that the four recommended guidance points were used least 90 per cent of cases eventually diagnosed with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prescribing is only one part of the approach to managing young people with persisting ADHD symptoms. There are various models of delivering care for older adolescents and adults with ADHD including extension of child mental health services, youth services and specific adult ADHD services, and recent recommendations on transition have been made by the UK Adult ADHD Network (UKAAN) [ 26 28 ]. However, the evidence regarding the effectiveness of different service models in improving outcomes needs to be strengthened—a systematic review in 2015 by Paul and colleagues concluded that there was currently no ‘high quality’ evidence to support the use of any particular transition care models [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction – Neurodevelopmental disorders). Three studies included young people with ASD (Laxman, Taylor, DaWalt, Greenberg, & Mailick, 2019; Merrick et al., 2020; Tunesi, Bosio, & Russo, 2019), four included young people with any neurodevelopmental condition (Asl, 2014; Maslow, 2016; Patwardhan, Singh, & Kanster, 2019; Singh et al., 2021), one focused on learning disabilities (Sharif, 2021), one on hyperkinetic disorder (Blasco‐Fontecilla et al., 2012) and the remainder focussed on ADHD (Ayyash et al., 2018; Eke et al., 2019; Eke et al., 2018; Heron et al., 2020; Janssens et al., 2020; Magon, Latheesh, & Muller, 2015; McCarthy et al., 2009; McNicholas & Singh, 2015; Moosa & Sandhu, 2015; Ogundele, 2013; Ogundele & Omenaka, 2012; Price, Newlove‐Delgado, et al., 2019; Reale et al., 2018; Reale, Frassica, Gollner, & Bonati, 2015; Tatlow‐Golden et al., 2018). However, most studies included young people with comorbidity, including those with comorbid ADHD/ASD.…”
Section: Transition For Those With Neurodevelopmental Disordersmentioning
confidence: 99%